NKp44-Derived Peptide Binds Proliferating Cell Nuclear Antigen and Mediates Tumor Cell Death - Shemesh, Avishai; Kundu, Kiran; Peleg, Refael; Yossef, Rami; Kaplanov, Irena; Ghosh, Susmita; Khrapunsky, Yana; Gershoni-Yahalom, Orly; Rabinski, Tatiana; Cerwenka, Adelheid; Atlas, Roee; Porgador, Angel (Frontiers in Immunology, 2018)
Proliferating Cell Nuclear Antigen (PCNA) is considered as a hub protein and is a key regulator of DNA replication, repair, cell cycle control and apoptosis. PCNA is over-expressed in many cancer types and PCNA-overexpression is correlated with cancer virulence. Membrane-associated PCNA is a ligand for the NKp44 (NCR2) innate immune receptor. The purpose of this study was to characterize the PCNA binding site within NKp44. We have identified NKp44-derived linear peptide (pep8), which can specifically interact with PCNA and partly block the NKp44-PCNA interaction. We then tested whether NKp44-derived pep8 fused to cell-penetrating peptides can be employed for targeting the intracellular PCNA for the purpose of anti-cancer therapy. Treatment of tumor cells with NKp44-derived pep8, fused to R11-NLS cell penetrating peptide (R11-NLS-pep8), reduced cell viability and promoted cell death, in a variety of murine and human cancer cell lines. Administration of R11-NLS-pep8 to tumor-bearing mice suppressed tumor growth in the 4T1 breast cancer and the B16 melanoma in vivo models. We therefore identified the NKp44 binding site to PCNA and further developed an NKp44-peptide based agent that can inhibit tumor growth through interfering with the function of intracellular PCNA in the tumor cell.